Dent-to-Stiffener Evaluation Concept for Thin-Walled Steel Cylinders - Akarsu Oğuzhan; Bayrak Barış; Kiliç Mahmut; Maali Mahyar; Aydin Abdulkadir Cüneyt (Architecture, Civil Engineering, Environment, 2023)
Defects/imperfections can occur during manufacturing, assembly, welding, and other processes, which can reduce the critical buckling load. However, the axial buckling load is beyond the scope of this work, and there are many studies on the stiffening effect of longitudinal dents. This concept combined the idea of the dent-to-stiffener evaluation concept for thin-walled steel cylinders. This study aims to transform the dents into artificial dents for a stiffening effect on the buckling phenomena. For this purpose, 37 thin-walled steel cylinder models, including the perfect model, were designed for varying dent shapes, dent widths, dent depths, dent lengths, and dent angles. The study also contributed to the effect of dent parameters on the critical buckling load of thin-walled steel cylinders. In particular, increasing the initial buckling will motivate the industry to convert dents into stiffeners with small artificial touches to enhance the longevity of the structure. The results showed that the introduction of certain artificial dents can significantly increase the critical buckling load of cylinders, thus improving their resistance against buckling, which has significant implications for various industries that use thin-walled steel cylinders in their structures. The proposed simulations for transforming dents into artificial stiffeners can be a valuable tool for enhancing the longevity and safety of thin-walled steel cylinders and other structures.